Preparation method of multi-quaternary ammonium cation type fiber and application of multi-quaternary ammonium cation type fiber in nuclear medical waste liquid

Polyacrylonitrile fibers were modified by hydrothermal reaction method to prepare multiquaternary ammonium cationic fibers, which solved the problem of low removal efficiency of iodine contaminated waste liquid in the prior art, and achieved efficient and rapid iodine ion adsorption and recycling.

CN119877276AActive Publication Date: 2025-04-25SOUTHWEAT UNIV OF SCI & TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510172190.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-25
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove iodine-contaminated nuclear medical waste liquid, and traditional materials have shortcomings in adsorption rate and capacity.

Method used

Polyacrylonitrile fibers are modified by hydrothermal reaction method to prepare multiquaternary ammonium cationic fibers. The fiber has ultra-fast adsorption rate and extremely high adsorption capacity, and has the advantages of cyclic regeneration and rapid adsorption.

Benefits of technology

It has achieved efficient capture of iodine ions in nuclear medical waste liquid, with extremely fast adsorption rate, achieving adsorption equilibrium within 30 seconds, high adsorption capacity, and good circulation and regeneration performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877276A_ABST
    Figure CN119877276A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of multi-quaternary ammonium cation type fibers and application of the multi-quaternary ammonium cation type fibers in nuclear medical waste liquid. The preparation method comprises the steps that polyacrylonitrile fibers are subjected to activation pretreatment and dried to constant weight; adding an amination reagent and a cross-linking agent into the dried polyacrylonitrile fibers, and carrying out constant-temperature reaction to obtain modified polyacrylonitrile fibers; soaking the modified polyacrylonitrile fiber in an acid solution, washing to be neutral, and drying to constant weight to obtain a polyaminated polyacrylonitrile fiber; adding an organic solvent and halogenated hydrocarbon into the polyaminated polyacrylonitrile fiber, and reacting to obtain a modified fiber; the modified fiber is soaked in a mixed solution of acidic sodium chloride for desorption, washed to be neutral and dried to be constant in weight, and the multi-quaternary ammonium cation type fiber is obtained. The synthesis method is simple and easy to operate, batch synthesis can be achieved, the prepared multi-quaternary ammonium cation type fiber is extremely high in iodine ion adsorption rate and high in adsorption capacity, adsorption equilibrium can be achieved within 30 s, and radioactive iodine in nuclear medical waste liquid can be efficiently captured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste liquid purification materials, and more specifically, the invention relates to a preparation method of polyquaternary ammonium cationic fiber and its application in nuclear medical waste liquid. Background Art

[0002] Iodine has 37 known isotopes ( 108 I to 144 I), all isotopes decay, except 127 I, which is a stable isotope of iodine, is used in the applications listed below. In chemistry, 127 I is mainly used in oxidation reactions. In medicine, KI ( 127 I) is used as a supplement to protect against radioactive iodine. A radioactive isotope of iodine, 123 I and 125 I, is used as a nuclear imaging tracer to assess thyroid physiological function, while 131 I (half-life 8 days) is used to treat thyroid cancer or other physiological conditions of the thyroid gland (e.g., hyperthyroidism). 131 I) has saved many lives. Radioactive and stable isotopes of iodine are widely present in our environment, including soil and freshwater sources, and the generation of iodine waste is inevitable, so cost-effective and efficient technologies must be developed to remove iodine from the environment. Iodine-contaminated wastewater can contaminate drinking water and groundwater, which will increase the risk of thyroid cancer. Typically, exposure to iodine may cause short-term effects such as (1) irritation, skin burns, and eye damage; (2) fumes that may severely irritate the nose and throat; and (3) headaches, metallic taste, nausea, vomiting, diarrhea, and abdominal pain. Prolonged exposure or higher doses will lead to chronic health effects, including cancer and reproductive harm.

[0003] Therefore, in order to mitigate these environmental impacts, several researchers have made great efforts to address this issue by developing new materials to explore different chemical / physical methods to remove iodine from our environment. More specifically, the reported studies focus on developing different iodine removal strategies and materials, such as membrane filters, electrodialysis, electrochemical techniques, etc. Adsorption materials include nanoparticles, layered double hydroxides, silver impregnated activated carbon, ion exchange fibers, ion exchange resins, etc.

[0004] The present invention adopts a hydrothermal reaction method to modify polyacrylonitrile fiber to obtain a multi-quaternary ammonium cationic fiber. In addition to an ultra-fast adsorption rate and an extremely high adsorption capacity, the fiber also has the advantages of recycling and ultra-fast adsorption. As a new generation of environmentally friendly materials, it has great application prospects and social and economic effects. Summary of the invention

[0005] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.

[0006] In order to achieve these purposes and other advantages according to the present invention, a polyquaternary ammonium cationic fiber is provided, and its structural formula is:

[0007]

[0008] Wherein, X includes but is not limited to one of nitrogen, bromine, fluorine and phosphorus.

[0009] Preferably, the method comprises the following steps:

[0010] Step 1: pre-activate the polyacrylonitrile fiber with a 0.1-1.0 mol / L NaOH solution, and then dry it in a 40-80° C. constant temperature oven to a constant weight;

[0011] Step 2: weigh the polyacrylonitrile fiber pre-treated and dried in step 1 and add it to a polytetrafluoroethylene-lined reactor, then add an amination agent and a cross-linking agent, and react at a constant temperature of 120 to 160° C. for 6.0 to 12.0 hours to obtain modified polyacrylonitrile fiber;

[0012] Step 3: soaking the modified polyacrylonitrile fiber obtained in step 2 in a low concentration acid solution for 0.5 to 2.0 hours, washing with deionized water until neutral, and drying in a constant temperature oven to constant weight to obtain polyamined polyacrylonitrile fiber;

[0013] Step 4: adding the polyamined polyacrylonitrile fiber obtained in step 3 into a polytetrafluoroethylene-lined reactor, then adding a certain volume of organic solvent and halogenated hydrocarbon, and reacting at 25-65° C. for 6.0-12.0 hours to obtain modified fiber;

[0014] Step 5: Soak the modified fiber obtained in step 4 in a mixed solution of 0.1-2.0 mol / L acidic sodium chloride for desorption, then wash with deionized water until neutral, and dry in a constant temperature oven to constant weight to obtain polyquaternary ammonium cationic fiber.

[0015] Preferably, in the step 1, the usage ratio of the polyacrylonitrile fiber and the NaOH solution is 0.2-1.0 g:1 L.

[0016] Preferably, in the step 2, the amination agent includes but is not limited to any one or more of 3-dimethylaminopropylamine, N,N-diethylbutane-1,4-diamine, triethylamine, N,N-dimethyl-1,3-diaminopropane, and dimethyldipropylenetriamine;

[0017] The cross-linking agent includes, but is not limited to, any one of ethylenediamine, diethylenetriamine, triethylenetetramine, and tetraethylenepentamine.

[0018] Preferably, in the step 2, the usage ratio of polyacrylonitrile fiber, amination reagent and cross-linking agent is 0.5-1 g: 0.0-50.0 mL: 1.0-5.0 mL.

[0019] Preferably, in step three, the acidic solution includes but is not limited to any one or more of nitric acid, sulfuric acid, hydrochloric acid, and phosphoric acid, and the concentration of the acidic solution is 0.1 to 1.0 mol / L.

[0020] Preferably, in step 4, the usage ratio of modified polyacrylonitrile fiber, organic solvent and halogenated hydrocarbon is 0.5-1.0 g:20.0-40.0 mL:0.5-2.0 mL.

[0021] Preferably, in step 4, the organic solvent includes but is not limited to any one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and acetonitrile.

[0022] Preferably, in step 4, the halogenated hydrocarbon includes but is not limited to any one or more of methyl bromide, methyl iodide, ethyl bromide and ethyl iodide.

[0023] The invention discloses an application of a polyquaternary ammonium cationic fiber, which is applied to the adsorption and removal of iodine ions by nuclear medical waste liquid.

[0024] The present invention has at least the following beneficial effects:

[0025] The polyquaternary ammonium cationic fiber synthesis method provided by the present invention is simple and easy to operate, and can realize batch synthesis.

[0026] The polyquaternary ammonium cationic fiber provided by the present invention has an extremely fast adsorption rate of iodine ions and can reach adsorption equilibrium in less than 30 seconds.

[0027] The polyquaternary ammonium cationic fiber provided by the present invention has high adsorption capacity and good ultra-fast adsorption ability, and can efficiently capture radioactive iodine in nuclear medical waste liquid.

[0028] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a graph showing the adsorption capacity of iodide ions for the polyquaternary ammonium cationic fiber under different pH conditions in Example 1;

[0030] Figure 2 This is a SEM image of the original polyacrylonitrile fiber in step 1 of Example 1;

[0031] Figure 3 This is a SEM image of the polyquaternary ammonium cationic fiber after being soaked in 0.1 mol / L HCl in step 5 of Example 1;

[0032] Figure 4 This is a SEM image of the polyquaternary ammonium cationic fiber after adsorbing iodine waste liquid in Example 1;

[0033] Figure 5 This is a time gradient diagram of the adsorption of iodide ions by the polyquaternary ammonium cationic fiber in Example 1;

[0034] Figure 6 is a graph showing the concentration gradient of iodine ions adsorbed by the polyquaternary ammonium cationic fiber in Example 1;

[0035] Figure 7 : is the ionic strength influence diagram of the multi-quaternary ammonium cationic fiber in Example 1;

[0036] Figure 8 This is a recycling diagram of the multi-quaternary ammonium cationic fiber in Example 1;

[0037] Fig. 9 The adsorption performance of the material samples prepared in Example 1, Comparative Examples 1 to Comparative Examples 3 and the polyacrylonitrile sample is compared. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.

[0039] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0040] Example 1

[0041] A method for preparing polyquaternary ammonium cationic fiber comprises the following steps:

[0042] Step 1: 0.5 g of polyacrylonitrile fiber was pre-activated with 0.5 L of 0.1 mol / L NaOH, and then dried in a 60° C. constant temperature oven to constant weight.

[0043] Step 2: Weigh 0.5 g of activated pretreated polyacrylonitrile fiber and add it into a 50.0 mL hydrothermal reactor, then add 25.0 mL of 3-dimethylaminopropylamine and 1.0 mL of triethylenetetramine, and react at 155° C. for 6 h to obtain modified polyacrylonitrile fiber;

[0044] Step 3, soaking the modified polyacrylonitrile fiber in a 0.1 mol / L HCl solution for 30 min, washing with deionized water until neutral, and drying in a constant temperature oven to constant weight to obtain polyamined polyacrylonitrile fiber;

[0045] Step 4: Weigh 0.8 g of polyamined polyacrylonitrile fiber and add it into a 50.0 ml hydrothermal reactor, then add 25.0 ml of N, N-dimethylformamide and 1.0 ml of methyl iodide and react in an oven at 40 ° C for 6.0 h to obtain modified fiber.

[0046] Step 5: After the reaction is completed, the modified fiber is washed with anhydrous ethanol, and then the modified fiber is immersed in 0.1 mol / L HCl and stirred for 30 min, washed with deionized water, and dried in a constant temperature oven at 60°C to constant weight to obtain a polyquaternary ammonium cationic fiber. The polyquaternary ammonium cationic fiber obtained in this embodiment is referred to as QA-PAN.

[0047] The polyquaternary ammonium cationic fiber prepared in this embodiment was subjected to an iodide ion adsorption experiment under different pH conditions. The experimental method was as follows: the pH of a centrifuge tube containing 25 mL of a 100 mg / L iodide ion solution was adjusted to 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, or 11.0, and 20 mg of the polyquaternary ammonium cationic fiber was added thereto. The solution was then placed on a constant temperature oscillating box at 25°C for adsorption for 12 hours, and 1 mL of the supernatant was taken and the iodide ion concentration of the remaining solution was determined using an ultraviolet spectrophotometer.

[0048] like Figure 1 As shown, the results show that the polyquaternary ammonium cationic fiber prepared by the present invention maintains a removal rate of nearly 90% for iodide ions at pH = 3.0-11.0, and has a good adsorption capacity, and the maximum iodine ion adsorption capacity is: 113.5 mg / g.

[0049] For the polyquaternary ammonium cationic fibers prepared in this example, electron microscopy (SEM) was performed on them. Figure 2 The SEM image of the original polyacrylonitrile fiber is shown, and it can be seen that the fiber surface is relatively rough, irregular and has a small amount of protrusions; Figure 3 This is the SEM image of polyquaternary ammonium cationic fiber after being immersed in 0.1 mol / L HCl. After modification, the fiber surface becomes smooth and the overall structure remains intact. Figure 4 The SEM image of 20 mg of polyquaternary ammonium cationic fiber after adsorbing 25 mL of 100 mg / L iodine waste liquid at a pH of about 7.0 shows that the surface of the fiber becomes rough after adsorbing iodine ions, which also proves that the fiber does have an adsorption effect on iodine ions.

[0050] For the polyquaternary ammonium cationic fiber prepared in this example, a time gradient experiment was conducted, and the steps were as follows:

[0051] Add 20 mg of polyquaternary ammonium cationic fiber into a centrifuge tube containing 25 mL of 100 mg / L iodide ion solution, set multiple time nodes (10s, 20s, 30s, 1min, 2min, 5min, 10min, 20min, 30min, 60min, 120min), and then place it in a 25°C constant temperature oscillation box for adsorption. When the time node is reached, take 1 mL of supernatant and use a UV spectrophotometer to determine the iodine ion concentration of the remaining solution.

[0052] like Figure 5 As shown, the results show that the polyquaternary ammonium cationic fiber prepared in this example reaches adsorption equilibrium within 30 seconds and has the characteristic of fast adsorption rate.

[0053] For the polyquaternary ammonium cationic fiber prepared in this example, an iodide ion concentration gradient experiment was performed, and the steps were as follows:

[0054] 20 mg of polyquaternary ammonium cationic fiber was added into a centrifuge tube containing 25 mL of iodine ion solution of different concentrations, and multiple concentration gradients (100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 600 mg / L, 800 mg / L, 1000 mg / L) were set. Then, the tube was placed in a 25°C constant temperature oscillating box for adsorption. After time equilibrium, 1 mL of supernatant was taken and the iodine ion concentration of the remaining solution was determined by ultraviolet spectrophotometer.

[0055] like Figure 6 As shown, the results show that: with the increase of concentration gradient, the adsorption capacity of polyquaternary ammonium cationic fiber for iodine ions in iodine-containing solution also increases, and the maximum equilibrium adsorption capacity can reach 645.8mg-1g.

[0057] For the polyquaternary ammonium cationic fiber prepared in this example, an adsorption experiment with different ionic strengths was performed, and the steps were as follows:

[0058] Add 20 mg of polyquaternary ammonium cationic fiber into a centrifuge tube containing 25 mL of 0.0008 mol / L iodide ion solution, add 0, 0.001, and 0.01 mol / L sodium chloride solutions thereto, and then place it in a 25°C constant temperature oscillating box for adsorption. After time equilibrium, take 1 mL of supernatant and determine the iodine ion concentration of the remaining solution using a UV spectrophotometer.

[0059] like Figure 7As shown, the results show that: with the increase of sodium chloride concentration gradient, the adsorption capacity of polyquaternary ammonium cationic fiber for iodine ions in iodine-containing solution does not change much, indicating that the ion exchange fiber has a certain ability to resist ion interference.

[0060] For the polyquaternary ammonium cationic fiber prepared in this embodiment, a recycling experiment was performed on it, and the steps are as follows:

[0061] Add 20 mg of polyquaternary ammonium cationic fiber into a centrifuge tube containing 25 mL of 50 mg / L iodide ion solution, and then place it in a 25°C constant temperature oscillating box for adsorption. After the time is balanced, take 1 mL of the supernatant and use a UV spectrophotometer to determine the iodine ion concentration of the remaining solution. Then collect the adsorbed fibers and desorb and regenerate them with 1 mol / L NaCl, and then repeat the above operation.

[0062] like Figure 8 As shown, the results show that after multiple adsorption and desorption, the multi-quaternary ammonium cationic fiber can still maintain a high removal rate for iodide ions, indicating that the ion exchange fiber has good recycling regeneration performance.

[0063] Comparative Example 1

[0064] This comparative example provides a method for preparing polyamined polyacrylonitrile fiber, comprising the following steps:

[0065] Step 1: 0.5 g of polyacrylonitrile fiber was pre-activated with 0.5 L of 0.1 mol / L NaOH, and then dried in a 60° C. constant temperature oven to constant weight.

[0066] Step 2: Weigh 0.5 g of activated pretreated polyacrylonitrile fiber and add it into a 50.0 mL hydrothermal reactor, then add 25.0 mL of 3-dimethylaminopropylamine and 1.0 mL of triethylenetetramine, and react at 155° C. for 6 h to obtain modified polyacrylonitrile fiber;

[0067] Step 3: Soak the modified polyacrylonitrile fiber in 0.1 mol / L HCl solution for 30 min, wash it with deionized water until it becomes neutral, and dry it in a constant temperature oven to a constant weight to obtain polyamine polyacrylonitrile fiber, which is recorded as A-PAN.

[0068] Comparative Example 2

[0069] This comparative example provides a method for preparing acidified non-quaternary ammonium cationic fiber, comprising the following steps:

[0070] Step 1: 0.5 g of polyacrylonitrile fiber was pre-activated with 0.5 L of 0.1 mol / L NaOH, and then dried in a 60° C. constant temperature oven to constant weight.

[0071] Step 2: Weigh 0.5 g of activated pretreated polyacrylonitrile fiber and add it into a 50.0 mL hydrothermal reactor, then add 25.0 mL of 3-dimethylaminopropylamine and 1.0 mL of triethylenetetramine, and react at 155° C. for 6 h to obtain modified polyacrylonitrile fiber;

[0072] Step 3: Weigh 0.8 g of modified polyacrylonitrile fiber and add it into a 50.0 ml hydrothermal reactor, then add 25.0 ml of N, N-dimethylformamide and 1.0 ml of methyl iodide and react in an oven at 40° C. for 6.0 h to obtain a fiber product;

[0073] Step 4: After the reaction is completed, the fiber product is washed with anhydrous ethanol, then immersed in 0.1 mol / L HCl and stirred for 30 min, washed with deionized water, and dried in a constant temperature oven at 60°C to constant weight to obtain acidified unquaternary ammonium cationic fiber, recorded as unQA-PAN.

[0074] Comparative Example 3

[0075] This comparative example provides a method for preparing unacidified polyamined polyacrylonitrile fiber, comprising the following steps:

[0076] Step 1: 0.5 g of polyacrylonitrile fiber was pre-activated with 0.5 L of 0.1 mol / L NaOH, and then dried in a 60° C. constant temperature oven to constant weight.

[0077] Step 2: Weigh 0.5 g of activated pretreated polyacrylonitrile fiber and add it to a 50.0 mL hydrothermal reactor, then add 25.0 mL of 3-dimethylaminopropylamine and 1.0 mL of triethylenetetramine, and react at a constant temperature of 155° C. for 6 hours to obtain unacidified polyamined polyacrylonitrile fiber (i.e., the modified polyacrylonitrile fiber obtained in step 2 of Example 1), which is recorded as unA-PAN.

[0078] The adsorption performance of QA-PAN prepared in Example 1, A-PAN prepared in Comparative Examples 1 to 3, unQA-PAN, unA-PAN and polyacrylonitrile (PAN) under the same conditions is shown in FIG. Fig. 9 The specific adsorption method is as follows: the experimental method prepared in Example 1 is as follows: set up 5 groups of 450mg / L 25mL iodide ion solutions, adjust the pH to 7.0, and then add 10mg of QA-PAN, A-PAN, unQA-PAN, unA-PAN, PAN to one group of iodide ion solutions for adsorption experiment, place it on a 25℃ constant temperature oscillating box for adsorption for 10min, take 1mL of supernatant and use a UV spectrophotometer to determine the iodine ion concentration of the remaining solution. Fig. 9It can be seen that the adsorption capacity of tertiary amine on unA-PAN increased from 64.1 mg g -1 Increased to 208.8 mg g -1 , which improved the adsorption performance of neutral amines to a certain extent. Secondly, the presence of protonated amines was increased by HCl immersion, which greatly improved the adsorption performance of the adsorbent. In particular, the adsorption capacity of A-PAN and QA-PAN was almost 7.5 and 8.1 times that of unA-PAN. The adsorption capacity of QA-PAN was slightly higher than that of A-PAN because of the co-existence of protonated secondary amines and quaternary ammonium salts, which enhanced the adsorption of I in water. - adsorption capacity.

[0079] Positive charge density (PCD) (mmol / g) is defined as N per gram of material. + The number of moles can be calculated based on the XPS results as follows:

[0080]

[0081] Where m N (wt%) is the mass percentage of nitrogen (Table 1). N (at%) is the N content of each material + The molar content (Table 2), M N is the atomic mass of nitrogen.

[0082] The positive charge densities of unA-PAN, A-PAN, unQA-PAN, and QA-PAN were calculated to be 0, 4.2, 2.4, and 4.6 mmol g, respectively. -1 According to the positive charge density, the theoretical adsorption capacity of QA-PAN can reach 584.2 mg g -1 , and the experimental adsorption capacity reached 645.8 mg g -1 , indicating that the iodine ions captured by QA-PAN through electrostatic interaction account for about 91%, so it is speculated that there are other interaction forces, such as hydrogen bonding, which account for about 9%.

[0083] Table 1. Nitrogen contents on unA-PAN, A-PAN, unQA-PAN and QA-PAN obtained from XPS test.

[0084]

[0085] Table 2. Contents of different functional groups on unA-PAN, A-PAN, unQA-PAN and QA-PAN obtained based on XPS N1s spectrum analysis.

[0086]

[0087] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.

[0088] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.

Claims

1. A polyquaternary ammonium cationic fiber, characterized in that: Its structural formula is: Wherein, X includes but is not limited to one of nitrogen, bromine, fluorine and phosphorus.

2. A method for preparing the polyquaternary ammonium cationic fiber according to claim 1, characterized in that: The following steps are involved: Step 1: pre-activate the polyacrylonitrile fiber with a 0.1-1.0 mol / L NaOH solution, and then dry it in a 40-80° C. constant temperature oven to a constant weight; Step 2: weigh the polyacrylonitrile fiber pre-treated and dried in step 1 and add it to a polytetrafluoroethylene-lined reactor, then add an amination agent and a cross-linking agent, and react at a constant temperature of 120 to 160° C. for 6.0 to 12.0 hours to obtain modified polyacrylonitrile fiber; Step 3: soaking the modified polyacrylonitrile fiber obtained in step 2 in a low concentration acid solution for 0.5 to 2.0 hours, washing with deionized water until neutral, and drying in a constant temperature oven to constant weight to obtain polyamined polyacrylonitrile fiber; Step 4: adding the polyamined polyacrylonitrile fiber obtained in step 3 into a polytetrafluoroethylene-lined reactor, then adding a certain volume of organic solvent and halogenated hydrocarbon, and reacting at 25-65° C. for 6.0-12.0 hours to obtain modified fiber; Step 5: Soak the modified fiber obtained in step 4 in a mixed solution of 0.1-2.0 mol / L acidic sodium chloride for desorption, then wash with deionized water until neutral, and dry in a constant temperature oven to constant weight to obtain polyquaternary ammonium cationic fiber.

3. The method for preparing polyquaternary ammonium cationic fiber according to claim 2, characterized in that: In the step 1, the usage ratio of the polyacrylonitrile fiber and the NaOH solution is 0.2-1.0 g:1 L.

4. The method for preparing polyquaternary ammonium cationic fiber according to claim 2, characterized in that: In the step 2, the amination reagent includes but is not limited to any one or more of 3-dimethylaminopropylamine, N,N-diethylbutane-1,4-diamine, triethylamine, N,N-dimethyl-1,3-diaminopropane, and dimethyldipropylenetriamine; The cross-linking agent includes, but is not limited to, any one of ethylenediamine, diethylenetriamine, triethylenetetramine, and tetraethylenepentamine.

5. The method for preparing polyquaternary ammonium cationic fiber according to claim 2, characterized in that: In the step 2, the usage ratio of polyacrylonitrile fiber, amination reagent and cross-linking agent is 0.5-1 g: 0.0-50.0 mL: 1.0-5.0 mL.

6. The method for preparing polyquaternary ammonium cationic fiber according to claim 2, characterized in that: In step 3, the acidic solution includes but is not limited to any one or more of nitric acid, sulfuric acid, hydrochloric acid, and phosphoric acid, and the concentration of the acidic solution is 0.1 to 1.0 mol / L.

7. The method for preparing polyquaternary ammonium cationic fiber according to claim 2, characterized in that: In the step 4, the usage ratio of modified polyacrylonitrile fiber, organic solvent and halogenated hydrocarbon is 0.5-1.0 g: 20.0-40.0 mL: 0.5-2.0 mL.

8. The method for preparing polyquaternary ammonium cationic fiber according to claim 2, characterized in that: In step 4, the organic solvent includes, but is not limited to, any one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and acetonitrile.

9. The method for preparing polyquaternary ammonium cationic fiber according to claim 2, characterized in that: In step 4, the halogenated hydrocarbon includes but is not limited to any one or more of methyl bromide, methyl iodide, ethyl bromide, and ethyl iodide.

10. An application of the polyquaternary ammonium cationic fiber according to claim 1, characterized in that: The polyquaternary ammonium cationic fiber is used for the adsorption and removal of iodide ions by nuclear medical waste liquid.

Citation Information

Patent Citations

  • Preparation method of novel heavy metal chelate fiber

    CN105833845A

  • Method for preparing amphoteric antibacterial ion exchange fibers

    CN106049054A

  • Preparation method of chelated polyacrylonitrile fiber material

    CN109137503A

  • Polyacrylonitrile-based double-layer amidoxime modified functional fiber and preparation method thereof

    CN116716735A

  • Functionalized knitted fabric containing carboxyl and amino as well as preparation method and application of functional knitted fabric

    CN119083170A